Exploring spatiotemporal pattern in the association between short-term exposure to fine particulate matter and COVID-19 incidence in the continental United States: a Leroux-conditional-autoregression-based strategy - Liu, Shiyi; Ji, Shuming; Xu, Jianjun; Zhang, Yujing; Zhang, Han; Liu, Jiahe; Lu, Donghao (Frontiers in Public Health, 2023)
Numerous studies have reported a positive association between short-term exposure to fine particulate matter (PM2.5) and COVID-19 incidence. However, few studies have investigated the spatiotemporal heterogeneity in this association, which plays a crucial role in designing region-specific cost-effective public health policies and understanding the temporal trend in the association between PM2.5 and emerging infectious diseases such as COVID-19.The study outcome was state-level daily COVID-19 cases in 49 native USA states between April 1, 2020 and December 31, 2021. The exposure variable was the exponential moving average of PM2.5 with a lag of 0-14 days. The spatial distribution of association between PM2.5 and COVID-19 was investigated using a latest proposed strategy. First, a time-series generalized additive model was independently constructed to obtain a rough association for each state. Then, a conditional autoregressive model was used to smoothen the associations. Furthermore, the temporal trend in the association and the reasons underlying the spatiotemporal heterogeneity were investigated using a modified time-varying strategy.In all states, a positive association was observed between PM2.5 and COVID-19 incidence; nearly one-third of these states, mainly located in the middle-northern and northeastern regions, exhibited statistically significant. On average, a 1 µg/m 3 increase in PM2.5 concentration led to an increase in COVID-19 incidence by 0.92% (95%CI: 0.63% -1.23%). The temporal trend in the association presented a U-shape, with the weak association between September 1, 2020 and July 1, 2021 and the strongest association in the end of 2021. The vaccination rate was examined as a significant effect-modifying factor with a stronger positive association at a higher vaccination rate.Short-term exposure to PM2.5 is positively associated with COVID-19 incidence in the 3 USA. The stronger associations are distributed in the middle and eastern regions of the USA as well as in the post-pandemic era.